Continuing the conversation: 30 years of motivational interviewing dissemination. (July 2016) - Hall, Kate; Staiger, Petra K.; Simpson, Angela; Best, David; Lubman, Dan I.
Abstract : Commentary to:After 30 years of dissemination, have we achieved sustained practice change in motivational interviewing?